Coteaching in International Contexts
VII, 403 p. 36 illus., 17 illus. in color.
Keywords: Coteaching is two or more teachers teaching together, sharing responsibility for meeting the learning needs of students and, at the same time, learning from each other. Working as collaborators on every aspect of instruction, coteachers plan, teach and evaluate lessons together. Over the past decade, because coteaching can be highly beneficial to both students and teachers it has become an increasingly important element of science teacher education and is expanding into other content areas and educational settings. This edited book brings together ten years' work on the research and the practice of coteaching and its impact on teaching and learning, predominantly in the sciences. It includes contributions from Europe, United States and Australia and presents an doverview of theory and practice common to most studies.